Business Development Analysis of Zenio Fusion Food by using Business Modal Canvas - Zenio, Natasya Syahrany; Yuneline, Mirza Hedismarlina (Banking & Management Review, 2024)
Introduction/Main Objectives: The development of the culinary business is one of the many service businesses that are growing rapidly. There are many kinds of culinary in each region and each has its own characteristics like other types of traditions in general, food can also be combined. The purpose of this analysis is to determine the business development strategy to solve Zenio Fusion Food's problems. Background Problems: Zenio Fusion Food is a company engaged in the culinary field that combining different culinary elements and traditions, however, Zenio Fusion Food's business has a weakness in the marketing process that is not optimal which results in its business implementation being ineffective and not grow. Research Methods: The analytical method used is a qualitative descriptive method using a SWOT Matrix with a Business Model Canvas (BMC) method approach on Channels, Value Propositions, and Key Resources elements. With data collection techniques of observation, interviews and questionnaires. Finding/Results: The strategy that must be carried out based on the use of the two methods of the TOWS Matrix and the Business Model Canvas (BMC) obtained a strategy that is the company must focus more on Key Resources and Value Propositions. Conclusion: The strategy that must be carried out based is the company must focus more on marketing optimally by utilizing social media and implementing strategy determination on Key Resources elements such as physical assets and intellectual innovation of new recipes. As well as adding Value Propositions by adding menu variations that are more interesting and different from competitors.